Case of Colorectal Cancer Stage IVb (Dukes D) Presenting Emergently as a Strangulated Umbilical Hernia - Saad Warraich, Abdullah Al-Hudaib (International Journal of Innovative Research in Medical Science, 2017)
Colorectal cancer (CRC) is a lethal disease. Nearly 130,000 new cases are diagnosed each year in the United States, of which 95,270 are colon and the remainder rectal cancers (1). CRC patients may present with suspicious signs or symptoms; asymptomatic individuals are discovered by routine screening or emergency admission with intestinal obstruction, peritonitis or an acute gastrointestinal (GI) bleed (1). This case report discusses the case of 74 years old gentleman with CRC stage IVb (Dukes D), who presented as a strangulated umbilical hernia.